Strategy for Electronic Procurement of Good/Services Through Electronic Catalogues at the Ministry of Cooperatives - Rachmawati Yuslina; Neneng Sri Rahayu; Mala Sondang Silitonga (Green Publisher Indonesia, 2026)
Government procurement of goods and services is an important part of state financial management that requires transparency, efficiency, and accountability. This study was motivated by the suboptimal implementation of e-procurement through electronic catalogs (e-catalogs) at the Ministry of Cooperatives, as evidenced by the limited number of products on display, the unavailability of all necessary goods, prices that do not always reflect the lowest rates, and technical as well as administrative obstacles in the e-purchasing process. The purpose of this study is to identify the factors causing the suboptimal implementation of e-procurement and to formulate appropriate strategies to enhance its effectiveness. The research method employs a descriptive qualitative approach, with data collection techniques that include in-depth interviews, observation, and a literature review on the implementation of e-catalog. Data analysis was conducted using the Technology–Organization–Environment (TOE) framework and SWOT analysis. The results of the study show that technological factors (system complexity and IT infrastructure), organizational factors (human resource competencies), and environmental factors (regulations and inter-agency coordination) are the dominant elements influencing the implementation of e-catalogs. The recommendations of this study emphasize the need to strengthen the capacity of procurement human resources, develop a real-time, data-based electronic catalog system, and improve coordination between work units and providers to support the principles of good governance in government procurement of goods and services.